Specular reflective boundary conditions for Discrete Ordinate Methods in Periodic or Symmetric Geometries. (January 2016) - Cai, Jian; Modest, Michael F.
Abstract: In simulations of periodic or symmetric geometries, computational domains are reduced by imaginary boundaries that present the symmetry conditions. In Photon Monte Carlo methods, this is achieved by imposing specular reflective boundary conditions for the radiative intensity. In this work, a similar specular reflective boundary condition is developed for Discrete Ordinate Methods. The effectiveness of the new boundary condition is demonstrated by multiple numerical examples including plane symmetry and axisymmetry.